Indigenous secondary school recruitment into tertiary health professional study: a qualitative study of student and whānau worldviews on the strengths, challenges and opportunities of the Whakapiki Ake Project. Issue 1 (2nd January 2021) - Bryers, Carrie; Curtis, Elana; Tkatch, Melaney; Anderson, Anneka; Stokes, Kanewa; Kistanna, Sue; Reid, Papaarangi
ABSTRACT: Addressing the underrepresentation of Māori in the health workforce is expected to improve Māori health status and contribute to a reduction in Māori health inequities. This research aimed to understand the strengths, challenges and opportunities of the Whakapiki Ake Project (WAP) – an Indigenous tertiary recruitment programme that engages with Māori secondary school students (and their whānau) who wish to pursue a career in health. Two workshops framed within a Kaupapa Māori research approach were used for (1) current WAP students and (2) WAP whānau members attending the 2018 'Next STEPS to Uni' transitioning programme. Fourteen WAP students and 11 WAP whānau members participated. Thematic analysis of the workshop data identified that Indigenous student recruitment, embedded within a tertiary academic and institutional context and framed within a Kaupapa Māori positioning can positively support Indigenous health workforce development. In addition, the inclusion of whānau and whakawhanaungatanga within recruitment interventions over time supports Indigenous student recruitment and enhances cultural identity for students and their whānau members. Our study supports the investment in Indigenous student recruitment as an investment in anti-racism theory and practice.